Inline Progesterone Monitoring in the Dairy Industry. Issue 7 (July 2017) - Yu, Guang-Min; Maeda, Teruo
Abstract : An inline progesterone monitoring system that works automatically and provides real-time physiological information about lactating dairy cows for making farm management decisions is not only a novel tool for scientific research but also improves productivity, food safety, animal well-being, the environment, and the public perception of the dairy industry.